2018
DOI: 10.1177/1477370818772768
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of the seriousness of crime: Weighing the harm and the wrong

Abstract: The seriousness of crime or ‘crime seriousness’ bears on at least four areas of criminal policy (sentencing, criminalization, crime control and prevention) but is poorly defined. After providing a novel conceptualization of crime seriousness, this article explores the logic – or normative philosophical principles – behind the public’s assessment of crime seriousness and considers how the public’s logic aligns with legal principles and policy requirements. A general population survey administered in 2014 in Bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(86 citation statements)
references
References 46 publications
10
70
2
Order By: Relevance
“…More recently, Adriaenssen et al (2018) extended Warr's (1989) concept of harmfulness, building on Greenfield and Paoli's (2013) harm assessment framework. They conceptualized seriousness in terms of 1) the wrongfulness of a crime, defined as the severity of the violation of moral norms and sentiments implied by a criminal activity, 2) the severity of the harms of a crime, defined as the gravity of the injury or damage that the crime inflicts, 3) the incidence of the crime, defined as the frequency with which this type of crime actually happens, and 4) the incidence of the harms of a crime, defined as the frequency with which a type or range of harms occurs.…”
Section: The Components Of Perceived Crime Seriousnessmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Adriaenssen et al (2018) extended Warr's (1989) concept of harmfulness, building on Greenfield and Paoli's (2013) harm assessment framework. They conceptualized seriousness in terms of 1) the wrongfulness of a crime, defined as the severity of the violation of moral norms and sentiments implied by a criminal activity, 2) the severity of the harms of a crime, defined as the gravity of the injury or damage that the crime inflicts, 3) the incidence of the crime, defined as the frequency with which this type of crime actually happens, and 4) the incidence of the harms of a crime, defined as the frequency with which a type or range of harms occurs.…”
Section: The Components Of Perceived Crime Seriousnessmentioning
confidence: 99%
“…In order to explain variation beyond consensus, most studies analyze sociodemographic characteristics (e.g., gender, age, socio-economic status, educational level and ethnicity; see Stylianou, 2003). A few also consider victimization experiences (e.g., Adriaenssen et al, 2018Rosenmerkel, 2001Wolfgang et al, 1985), generally finding that victimization does not impact seriousness ratings for most crimes.…”
Section: Consensus and Difference In Public Perceptions Of Crime Serimentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical tests of this two-dimensional model have provided considerable empirical support (O'Connell & Wheelan, 1996;Rosenmerkel, 2001;Alter, Kernochan, & Darley, 2007;Fishman, Kraus & Cohen, 1986;Adriaenssen, Paoli, Karstedt, Visschers, Greenfield, & Pleysier, 2018), allowing it to become the dominant way of conceptualizing crime seriousness. And yet even the original study by Warr had reported that for some groups, and for some offences, the two-dimensional model may not be a good fit.…”
Section: Introductionmentioning
confidence: 99%
“…Findings also suggest that for some offences (such as common street crimes) seriousness is closely associated with wrongfulness, while for others (such as white collar offenses) it is closely associated with harmfulness (Rosenmerkel, 2001), suggesting that the construct of seriousness may rely on different set of evaluations for different types of offenses. In fact, a number of studies (Adriaenssen et al, 2018;Alter et al, 2007;O'Connell & Wheelan, 1996) have found wrongfulness to be a stronger predictor of offence seriousness, concluding that consequentialism is the less dominant approach to assessing the seriousness of crime.…”
Section: Introductionmentioning
confidence: 99%